Application of carbon-based material in preparation of medicine for treating or preventing diseases and pharmaceutical composition

Through the carbon dot-carbon nitride material loading metal ions, the bioavailability and safety of metal ions in the prior art are solved, and efficient hydrogen treatment and metal ion delivery are achieved, with good biocompatibility and therapeutic effects.

CN119564870APending Publication Date: 2025-03-07XIAMEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311136503.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When using metal ions to induce cancer cell death, it is difficult to ensure the bioavailability and safety of metal ions, and there is a lack of efficient delivery and treatment mechanisms.

Method used

Carbon dot-carbon nitride material loading metal ions is used to form a carrier in the carbon nitride material through carbon doping, and the metal ions are loaded on the carrier to achieve in vivo/in vitro metal ion delivery and efficient hydrogen treatment.

Benefits of technology

The efficiency of photocatalytic cracking of aquatic hydrogen is improved, and the synergistic mutual enhancement effect of metal ion delivery and hydrogen treatment is achieved, with high biocompatibility, biosafety and bioavailability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564870A_ABST
    Figure CN119564870A_ABST
Patent Text Reader

Abstract

The invention provides application of a carbon-based material in preparation of a medicine for treating or preventing diseases and a pharmaceutical composition. Diseases include metal ion level abnormity related diseases and / or hydrogen treatment diseases, the carbon-based material is a metal ion loaded carbon dot-carbon nitride material, in the metal ion loaded carbon dot-carbon nitride material, carbon dots are doped in a carbon nitride material to form a carrier, and metal ions are loaded on the carrier. The carbon dot-carbon nitride material loaded with the metal ions has a hydrogen production function and is loaded with the metal ions, so that in-vivo / in-vitro metal ion delivery and efficient hydrogen treatment are realized, and experiments find that the carbon-based material has relatively high biocompatibility, biological safety and bioavailability, and has a good application prospect. Meanwhile, photocatalytic hydrogen production and a metal ion death mechanism have a synergistic and reciprocal enhancement effect, so that a relatively good treatment or prevention effect is achieved on diseases related to abnormal metal ion levels and / or hydrogen treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of biomedicine, and specifically to the application of a carbon-based material in the preparation of a drug for treating or preventing a disease and a pharmaceutical composition. Background Art

[0002] Metal ion death has become a hot topic in recent years. Among them, copper death is a new cell death mechanism that is different from the known death mechanisms. It relies on mitochondrial respiration, induces lipid acylation protein aggregation and iron-sulfur cluster protein instability through copper, leading to proteotoxic stress, affecting the tricarboxylic acid (TCA) cycle, and ultimately leading to cell death.

[0003] When using the above-mentioned metal ion death mechanism to induce copper death of cancer cells, while considering the biocompatibility and biosafety of the metal ion carrier, it is also necessary to consider the release of metal ions to ensure the bioavailability of metal ions, thereby ensuring that the mechanism works fully. Summary of the invention

[0004] The present application provides the use of carbon-based materials in the preparation of drugs for treating or preventing diseases and pharmaceutical compositions, providing a new use of carbon-based materials.

[0005] The first aspect of the present application provides an application of a carbon-based material in the preparation of a drug for treating or preventing a disease, wherein the disease includes a disease related to abnormal metal ion levels and / or a disease that can be treated with hydrogen. The carbon-based material is a carbon dot-carbon nitride material loaded with metal ions. In the carbon dot-carbon nitride material loaded with metal ions, carbon dots are doped in the carbon nitride material to form a carrier, and the metal ions are loaded on the carrier.

[0006] In any embodiment of the first aspect, the disease associated with abnormal ion levels includes any one or more of diseases associated with abnormal copper ion levels, diseases associated with abnormal iron ion levels, diseases associated with abnormal manganese ion levels, diseases associated with abnormal zinc ion levels, and diseases associated with abnormal platinum ion levels; optionally, the disease associated with abnormal metal ions includes any one or more of cardiovascular diseases, neurodegenerative diseases, tumors, and cancers, and further preferably any one or more of breast cancer, colorectal cancer, lung cancer, liver cancer, prostate cancer, acute myeloid leukemia, glioma, neurodegenerative diseases, and bacterial infections; hydrogen therapy Diseases include any one or more of cardiovascular diseases, respiratory diseases, blood diseases, metabolic diseases, infections and neurodegenerative diseases; cardiovascular diseases include any one or more of atherosclerosis, hypertension, hypercholesterolemia and diabetic vascular disease; respiratory diseases include any one or more of upper respiratory tract infection, chronic obstructive pulmonary disease, pneumonia, bronchial asthma and lung cancer; blood diseases include any one or more of aplastic anemia, internal bleeding, pulmonary embolism, venous sinus thrombosis and cerebral infarction; neurodegenerative diseases include any one or more of Alzheimer's disease, Parkinson's disease and Huntington's disease (HD).

[0007] In any embodiment of the first aspect, the carbon dot-carbon nitride material loaded with metal ions includes any one or more of a carbon dot-carbon nitride material loaded with copper ions, a carbon dot-carbon nitride material loaded with iron ions, a carbon dot-carbon nitride material loaded with manganese ions, a carbon dot-carbon nitride material loaded with zinc ions, and a carbon dot-carbon nitride material loaded with platinum ions.

[0008] In any embodiment of the first aspect, the metal ion-loaded carbon dot-carbon nitride material is a metal ion-loaded carbon dot-carbon nitride nanosheet.

[0009] In any embodiment of the first aspect, in the carbon dot-carbon nitride material loaded with metal ions, the mass content of the metal ions is 1.0 wt%-3.0 wt%.

[0010] In any embodiment of the first aspect, the particle size of the carbon dot-carbon nitride material loaded with metal ions is between 60 nm and 200 nm.

[0011] The second aspect of the present application provides a pharmaceutical composition, which includes a carbon dot-carbon nitride material loaded with metal ions and a pharmaceutically acceptable excipient or auxiliary material, wherein the carbon dot-carbon nitride material loaded with metal ions serves as an active ingredient, the carbon dots are doped in the carbon nitride material to form a carrier, and the metal ions are loaded on the carrier.

[0012] In any embodiment of the first aspect, the carbon dot-carbon nitride material loaded with metal ions includes any one or more of a carbon dot-carbon nitride material loaded with copper ions, a carbon dot-carbon nitride material loaded with iron ions, a carbon dot-carbon nitride material loaded with manganese ions, a carbon dot-carbon nitride material loaded with zinc ions, and a carbon dot-carbon nitride material loaded with platinum ions.

[0013] In any embodiment of the first aspect, the metal ion-loaded carbon dot-carbon nitride material is a metal ion-loaded carbon dot-carbon nitride nanosheet.

[0014] In any embodiment of the first aspect, in the carbon dot-carbon nitride material loaded with metal ions, the mass content of metal ions is 1.0wt%-3.0wt%; and / or the particle size of the carbon dot-carbon nitride material loaded with metal ions is between 60nm-200nm.

[0015] In any embodiment of the first aspect, the dosage form of the pharmaceutical composition is any one of an oral preparation, an injection preparation, an inhalation preparation, and an external preparation.

[0016] In any embodiment of the first aspect, the diseases for which the pharmaceutical composition is used to treat or prevent include diseases associated with abnormal metal ion levels and / or diseases that can be treated with hydrogen.

[0017] In any embodiment of the first aspect, the diseases associated with abnormal metal ion levels include any one or more of diseases associated with abnormal copper ion levels, diseases associated with abnormal iron ion levels, diseases associated with abnormal manganese ion levels, diseases associated with abnormal zinc ion levels, and diseases associated with abnormal platinum ion levels; optionally, the diseases associated with abnormal metal ion levels include any one or more of cardiovascular diseases, neurodegenerative diseases, tumors, and cancers, and further preferably any one or more of breast cancer, colorectal cancer, lung cancer, liver cancer, prostate cancer, acute myeloid leukemia, glioma, neurodegenerative diseases, and bacterial infections; hydrogen therapy The diseases treated include any one or more of cardiovascular diseases, respiratory diseases, blood diseases, metabolic diseases, infections and neurodegenerative diseases; cardiovascular diseases include any one or more of atherosclerosis, hypertension, hypercholesterolemia and diabetic vascular disease; respiratory diseases include any one or more of upper respiratory tract infection, chronic obstructive pulmonary disease, pneumonia, bronchial asthma and lung cancer; blood diseases include any one or more of aplastic anemia, internal bleeding, pulmonary embolism, venous sinus thrombosis and cerebral infarction; neurodegenerative diseases include any one or more of Alzheimer's disease, Parkinson's disease and Huntington's disease (HD).

[0018] The metal ions are loaded on the carbon dot-doped carbon nitride material to improve the efficiency of photocatalytic water splitting to produce hydrogen. It can be seen that the above-mentioned carbon dot-carbon nitride material loaded with metal ions has both the function of producing hydrogen and loaded with metal ions, thus achieving in vivo / in vitro metal ion delivery and efficient hydrogen therapy. In addition, the experiment found that the carbon-based material has high biocompatibility, biosafety and bioavailability. At the same time, the photocatalytic hydrogen production and metal ion death mechanism have a synergistic and mutually beneficial enhancement effect, thereby having a good therapeutic or preventive effect on diseases related to abnormal metal ion levels and / or hydrogen therapy. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0020] Figure 1 The transmission electron micrographs of the materials prepared in Example 1 are shown, wherein a) is a transmission electron micrograph of carbon nitride, b) is a transmission electron micrograph of carbon dot-doped carbon nitride, and c) is a transmission electron micrograph of copper-loaded carbon dot-doped carbon nitride nanosheets.

[0021] Figure 2 The hydrated particle size distribution of aqueous solutions of CN, CDCN and Cu@CDCN of Example 1 is shown.

[0022] Figure 3 Digital photographs of aqueous solutions of CN, CDCN, and Cu@CDCN at a concentration of 1 mg / mL in Example 1 are shown.

[0023] Figure 4 The XRD spectra of CN, CDCN and Cu@CDCN of Example 1 are shown.

[0024] Figure 5 The UV-visible absorption spectra of CN, CDCN and Cu@CDCN of Example 1 are shown.

[0025] Figure 6 The photocatalytic hydrogen production capabilities of CN, CDCN and Cu@CDCN in Example 1 are shown, where a) is the variation curve of the absorption peak of CN; b) is the variation curve of the absorption peak of CDCN; c) is the variation curve of the absorption peak of Cu@CDCN; d) is a comparison diagram of the photocatalytic hydrogen production capabilities of CN, CDCN and Cu@CDCN.

[0026] Figure 7The photocatalytic hydrogen peroxide production ability test results of CN and CDCN in Example 1 are shown.

[0027] Figure 8 The results of the test on the ability of CN, CDCN and Cu@CDCN in Example 1 to consume reduced glutathione (GSH) are shown, wherein the Control group is a negative control group.

[0028] Fig. 9 The cellular uptake of CDCN in Example 1 is shown, wherein a) the cellular internalization of CDCN nanosheets after co-incubation with 4T1 cells for different time periods is quantitatively analyzed by flow cytometry. b) and c) the cellular localization behavior of CDCN nanosheets after co-incubation with 4T1 cells for 8 h.

[0029] Fig.10 The effects of different concentrations of CN, CDCN, and Cu@CDCN in Example 1 on the activity of 4T1 cells before and after illumination are shown, wherein a) shows the effects of different concentrations of CN on the activity of 4T1 cells before and after illumination, b) shows the effects of different concentrations of CDCN on the activity of 4T1 cells before and after illumination, and c) shows the effects of different concentrations of Cu@CDCN on the activity of 4T1 cells before and after illumination.

[0030] Fig.11 The apoptosis of CN, CDCN and Cu@CDCN cells after illumination and non-illumination treatment in Example 1 is shown (by Annexin V-FITC / PI staining and flow cytometer analysis), wherein the Control group is a negative control group, the Control+L group is a negative control group + illumination treatment, the CN group is a 4T1 cell and CN co-culture group, the CN+L group is a 4T1 cell and CN co-culture + illumination group, the CDCN group is a 4T1 cell and CDCN co-culture group, the CDCN+L group is a 4T1 cell and CDCN co-culture + illumination group, the Cu@CDCN group is a 4T1 cell and Cu@CDCN co-culture group, and the Cu@CDCN+L group is a 4T1 cell and Cu@CDCN co-culture + illumination group.

[0031] Fig.12 The intracellular consumption of GSH of CN, CDCN, and Cu@CDCN in Example 1 before and after light irradiation is shown.

[0032] Fig.13 The changes in intracellular ATP content of CN, CDCN, and Cu@CDCN in Example 1 before and after illumination are shown.

[0033] Fig.14The 4T1 cells of Example 1 were co-cultured with CN, CDCN or Cu@CDCN, and after being irradiated or not irradiated, confocal fluorescence microscope images (scale: 40 μm) were stained with a DCFH-DA probe (reactive oxygen probe to detect the production of reactive oxygen species), wherein the Control group was a negative control group, the Control+L group was a negative control group + irradiation treatment, the CN group was a 4T1 cell co-cultured with CN group, the CN+L group was a 4T1 cell co-cultured with CN + irradiation group, the CDCN group was a 4T1 cell co-cultured with CDCN group, the CDCN+L group was a 4T1 cell co-cultured with CDCN + irradiation group, the Cu@CDCN group was a 4T1 cell co-cultured with Cu@CDCN group, and the Cu@CDCN+L group was a 4T1 cell co-cultured with Cu@CDCN + irradiation group.

[0034] Fig.15 The lipid peroxidation levels of cells before and after illumination of CN, CDCN, and Cu@CDCN in Example 1 are shown, wherein the Control group is a negative control group.

[0035] Fig.16 The results of cell cycle changes after treatment with CN, CDCN and Cu@CDCN in Example 1 are shown, wherein a) shows the cell cycle analysis results of 4T1 cells after CN, CDCN and Cu@CDCN and light treatment, and b) shows the corresponding quantitative analysis results, wherein the Control group is a negative control group, the Control+L group is a negative control group + light treatment, the CN group is a 4T1 cell co-culture group with CN, the CN+L group is a 4T1 cell co-culture group with CN + light treatment, the CDCN group is a 4T1 cell co-culture group with CDCN, the CDCN+L group is a 4T1 cell co-culture group with CDCN + light treatment, the Cu@CDCN group is a 4T1 cell co-culture group with Cu@CDCN, and the Cu@CDCN+L group is a 4T1 cell co-culture group with Cu@CDCN + light treatment.

[0036] Fig.17 The scratch healing test results of 4T1 cells before and after light treatment with different concentrations of Cu@CDCN in Example 1 are shown in the left figure, where the scratch healing test microscopy results of 4T1 cells after different concentrations of Cu@CDCN and light treatment are shown, and the right figure shows the quantitative analysis results of the scratch healing rate obtained by ImageJ software analysis. The Control group is the negative control group, the Control+L group is the negative control group + light treatment, the Cu@CDCN group is the 4T1 cell and Cu@CDCN co-culture group, and the Cu@CDCN+L group is the 4T1 cell and Cu@CDCN co-culture + light treatment group

[0037] Fig.18The mitochondrial damage test results in Example 1 are shown, wherein a) JC-1 staining is shown and analyzed by flow cytometry for different treatments of mitochondrial membrane potential. The ratio of JC-1 aggregates to monomers (red / green fluorescence ratio) is an indicator of mitochondrial membrane polarization. b) 4T1 cell FDX1 protein content after different treatments is shown, wherein the Control group is a negative control group, the Control+L group is a negative control group+illumination treatment, the CN group is a 4T1 cell co-culture group with CN, the CN+L group is a 4T1 cell co-culture group with CN+illumination group, the CDCN group is a 4T1 cell co-culture group with CDCN, the CDCN+L group is a 4T1 cell co-culture group with CDCN+illumination group, the Cu@CDCN group is a 4T1 cell co-culture group with Cu@CDCN, and the Cu@CDCN+L group is a 4T1 cell co-culture group with Cu@CDCN+illumination group.

[0038] Fig.19 The results of routine blood analysis of mice in Example 1 are shown.

[0039] Fig. 20 The results of serum analysis of mice in Example 1 are shown.

[0040] Fig.21 The results of the hemolytic experiment on mice in Example 1 are shown.

[0041] Fig. 22 The results of intratumor analysis of tumor-bearing mice in Example 1 are shown. a) shows fluorescence imaging in 4T1 tumor-bearing mice after Cu@CDCN was labeled with indocyanine green (ICG) and administered via tail vein. b) shows the analysis results of the mean fluorescence intensity in the tumor at different times after intravenous injection of Cu@CDCN-ICG. c) shows the in vitro fluorescence images of major organs and tumors. d) shows the corresponding mean fluorescence intensity analysis results 24h and 36h after Cu@CDCN-ICG injection.

[0042] Fig.23 The in vivo tumor treatment effect of mice in Example 1 is shown, wherein a) shows the treatment method of tumor-bearing mice, b) shows the change of 4T1 tumor volume during treatment, c) shows the weight curve of each group of mice after 15 days of treatment, d) shows the 4T1 tumor mass after 15 days of treatment, and e) shows the 4T1 tumor photos extracted after 15 days of treatment (n=5 biological independent samples), wherein I Control is the PBS injection group, IIcontrol+L is the light treatment group after PBS injection, IIICDCN is the CDCN injection group, IV CDCN+L is the light treatment group after CDCN injection, V CuCDCN is the Cu@CDCN injection group, and VI CuCDCN+L is the light treatment group after Cu@CDCN injection.

[0043] Fig.24 The photocatalytic hydrogen production ability test results of CN of Example 1, CDCN-1 and CDCN-2 of Comparative Example 1 are shown.

[0044] Fig.25 The photocatalytic hydrogen peroxide production ability test results of CN of Example 1, CDCN-1 and CDCN-2 of Comparative Example 1 are shown.

[0045] Fig.26 The test results of the ability of CN and CDCN in Example 1, Cu@CDCN and Fe@CDCN in Example 2 to consume reduced glutathione (GSH) are shown, and the Control group is a negative control group.

[0046] Fig. 27 The test results of the effects of CN and CDCN in Example 1, and Cu@CDCN and Fe@CDCN in Example 2 on the activity of 4T1 cells are shown.

[0047] Fig.28 The test results of intracellular GSH consumption before and after illumination of CN and CDCN in Example 1, and Cu@CDCN and Fe@CDCN in Example 2 are shown, and the Control group is a negative control group. DETAILED DESCRIPTION

[0048] The following is a further detailed description of the implementation of the present application in conjunction with the accompanying drawings and examples. The detailed description of the following examples is used to exemplarily illustrate the principles of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described embodiments.

[0049] the term:

[0050] "Pharmaceutically acceptable excipient or lithium enrichment" includes, but is not limited to, any adjuvant, carrier, excipient, glidant, sweetener, diluent, preservative, dye / colorant, flavor enhancer, surfactant, wetting agent, dispersant, suspending agent, stabilizer, isotonic agent, solvent or emulsifier that has been approved by the Food and Drug Administration as acceptable for use in humans or livestock.

[0051] "Pharmaceutical composition" refers to a preparation of a compound of the present invention and a vehicle generally accepted in the art for delivering the biologically active compound to a mammal (eg, a human). Such a vehicle includes all pharmaceutically acceptable excipients therefor.

[0052] "Effective amount" or "therapeutically effective amount" refers to the amount of the compound according to the present invention, which, when applied to a patient in need thereof, is sufficient to achieve the treatment of a disease state, disease or disorder for which the carbon-based material is useful. Such an amount will be sufficient to cause the biological or medical response of the tissue system or patient sought by the researcher or clinician. The amount of the compound according to the present invention constituting the therapeutically effective amount will vary according to factors such as the following: the compound and its biological activity, the composition for administration, the time of administration, the route of administration, the compound excretion rate, the duration of treatment, the type of disease state or disease treated and its severity, the drug used in combination or in concert with the compounds of the present invention, and the patient's age, weight, general health, sex and diet. Those of ordinary skill in the art can routinely determine such a therapeutically effective amount based on their own knowledge, prior art and the present disclosure.

[0053] Unless otherwise indicated, the term "treatment" as used herein refers to reversing, alleviating, inhibiting its progress, or preventing the disorder or disease to which the term is applied, or one or more symptoms of such disorder or disease. The term "treatment" as used herein refers to the act of treating, because "treatment" is as described above. In some embodiments, the term "treatment" is intended to mean the use of a carbon-based material or a composition thereof according to the present invention to alleviate or eliminate the symptoms of a related disease.

[0054] "Prevention" (prevention or preventing) refers to any treatment of a disease or condition that results in clinical symptoms of the disease or condition not developing. The term "prevention" also includes administering a therapeutically effective amount of a compound or composition according to the invention before an individual is exposed to a virus (e.g., pre-exposure prophylaxis) to prevent the symptoms of the disease from occurring.

[0055] The term "subject" or "patient" refers to an animal, such as a mammal (including a human), that has been or is to be the subject of treatment, observation or experiment. The methods described herein can be used for human treatment and / or veterinary applications. In some embodiments, the subject is a mammal (or patient). In some embodiments, the subject (or patient) is a human, livestock (e.g., dogs and cats), farm animals (e.g., cattle, horses, sheep, goats and pigs) and / or laboratory animals (e.g., mice, rats, hamsters, guinea pigs, pigs, rabbits, cats, dogs and monkeys). In some embodiments, the subject (or patient) is a human. "A person (or patient) in need thereof" refers to a person who may suffer from or is suspected of suffering from a disease or condition that will benefit from certain treatments; for example, treatment with a carbon-based material disclosed herein or a composition thereof or a pharmaceutical composition comprising the above-mentioned ingredients according to the present application.

[0056] The present application provides an application of a carbon-based material in the preparation of a drug for treating or preventing a disease and a pharmaceutical composition.

[0057] In the first embodiment of the present application, there is provided an application of a carbon-based material in the preparation of a drug for treating or preventing a disease, wherein the disease includes a disease related to abnormal metal ion levels and / or a disease that can be treated with hydrogen, wherein the carbon-based material is a carbon dot-carbon nitride material loaded with metal ions, wherein the carbon dots are doped in the carbon nitride material to form a carrier, and the metal ions are loaded on the carrier.

[0058] The metal ions are loaded on the carbon dot-doped carbon nitride material to improve the efficiency of photocatalytic water splitting to produce hydrogen. It can be seen that the above-mentioned carbon dot-carbon nitride material loaded with metal ions has both the function of producing hydrogen and loaded with metal ions, thus achieving in vivo / in vitro metal ion delivery and efficient hydrogen therapy. In addition, the experiment found that the carbon-based material has high biocompatibility, biosafety and bioavailability. At the same time, the photocatalytic hydrogen production and metal ion death mechanism have a synergistic and mutually beneficial enhancement effect, thereby having a good therapeutic or preventive effect on diseases related to abnormal metal ion levels and / or hydrogen therapy.

[0059] The carbon nitride in the carbon-based material of the present application can be selected from any one or more combinations of CN, C2N, C3N, C3N4, C4N and C5N. In some embodiments, C3N4 is preferred.

[0060] In some embodiments of the present application, the diseases associated with abnormal metal ion levels include any one or more of diseases associated with abnormal copper ion levels, diseases associated with abnormal iron ion levels, diseases associated with abnormal manganese ion levels, diseases associated with abnormal zinc ion levels, and diseases associated with abnormal platinum ion levels; optionally, the diseases associated with abnormal metal ions include any one or more of cardiovascular diseases, neurodegenerative diseases, tumors, and cancers, and more preferably any one or more of breast cancer, colorectal cancer, lung cancer, liver cancer, prostate cancer, acute myeloid leukemia, glioma, neurodegenerative diseases, and bacterial infections. The above-mentioned carbon-based materials are used to deliver metal ions, and after the metal ions are released, the metal ion death mechanism is exerted to achieve a therapeutic effect on the corresponding disease.

[0061] In some embodiments of the present application, the diseases treated by the above hydrogen include any one or more of cardiovascular diseases, respiratory diseases, blood diseases, metabolic diseases, infections and neurodegenerative diseases; cardiovascular diseases include any one or more of atherosclerosis, hypertension, hypercholesterolemia and diabetic vascular disease; respiratory diseases include any one or more of upper respiratory tract infection, chronic obstructive pulmonary disease, pneumonia, bronchial asthma and lung cancer; blood diseases include any one or more of aplastic anemia, internal bleeding, pulmonary embolism, venous sinus thrombosis and cerebral infarction; neurodegenerative diseases include any one or more of Alzheimer's disease, Parkinson's disease and Huntington's disease (HD). All of the above diseases can be treated or assisted by hydrogen. The carbon-based material used in the present application is used as a photocatalyst to decompose water to produce hydrogen under the action of photocatalysis, and the produced hydrogen is used to achieve the treatment or prevention of the above diseases.

[0062] In some embodiments of the present application, the carbon point-carbon nitride material loaded with metal ions includes any one or more of the carbon point-carbon nitride material loaded with copper ions, the carbon point-carbon nitride material loaded with iron ions, the carbon point-carbon nitride material loaded with manganese ions, the carbon point-carbon nitride material loaded with zinc ions, and the carbon point-carbon nitride material loaded with platinum ions (such as the carbon point-carbon nitride material loaded with cisplatin). The carbon-based material loaded with different metal ions exerts the corresponding metal ion death mechanism to achieve the effect of treating or preventing the corresponding disease. The above-mentioned copper ions, iron ions, manganese ions, and zinc ions can all be loaded in the form of salts, such as loaded in the form of water-soluble organic salts or inorganic salts, including but not limited to chemical and biologically acceptable salt forms such as hydrochlorides, sulfates, citrates, and oxalates.

[0063] The metal ion-loaded carbon dot-carbon nitride material used in the present application can be a conventional metal ion-loaded carbon dot-carbon nitride material or a metal ion-loaded carbon dot-carbon nitride material prepared by a conventional method. In some embodiments of the present application, the above-mentioned metal ion-loaded carbon dot-carbon nitride material is a metal ion-loaded carbon dot-carbon nitride nanosheet, and the nanosheet structure is more conducive to metal ion delivery and hydrogen generation.

[0064] The carbon dots are mainly used to provide the effect of photocatalytic water splitting to produce hydrogen. The more carbon dots are contained, the better the carbon dots are. In order to avoid the influence of excessive carbon doping on the structure of carbon nitride nanosheets as much as possible, in some embodiments of the present application, the weight ratio of carbon dots to the raw materials for preparing carbon nitride materials is controlled to be 0.1:1000-1:1000 during the preparation of raw materials to control the quality of carbon dots in the carbon dots-carbon nitride material loaded with metal ions. Thus, as many carbon dots as possible are provided on the relatively stable carbon nitride nanosheets, thereby improving the photocatalytic effect.

[0065] Trace elements are important substances for maintaining life activities. Some metal ions are essential cofactors for many metal enzymes / proteins, but breaking the metal ion balance in cells will affect intracellular redox stress and mitochondrial damage, and ultimately cause cell death. Metal ions are mainly used to exert the death effect of metal ions. In some embodiments of the present application, the mass content of metal ions in the above-mentioned carbon dot-carbon nitride material loaded with metal ions is 1.0wt%-3.0wt%. Taking copper as an example, cancer cells are more sensitive to copper demand due to their more vigorous metabolism. By controlling the copper ion content in the carbon dot-carbon nitride material loaded with metal ions, the copper element in the carbon-based material is used to better promote the death of cancer cells, while avoiding the phenomenon of copper leakage caused by excessive copper content introduced, increasing the safety risk of normal cells.

[0066] The mass content of the above metal ions can be measured by ICP-OES.

[0067] In some embodiments of the present application, in order to improve the delivery efficiency of the material, the particle size of the carbon dot-carbon nitride material loaded with metal ions is selected to be between 60nm and 200nm, preferably. The above particle size is a hydrated particle size, and the hydrated particle size of the carbon dot-carbon nitride material loaded with metal ions in an aqueous solution can be tested using a Malvern laser particle size analyzer.

[0068] In a second embodiment of the present application, a pharmaceutical composition is provided, which includes a carbon dot-carbon nitride material loaded with metal ions and a pharmaceutically acceptable excipient or auxiliary material, wherein the carbon dot-carbon nitride material loaded with metal ions serves as an active ingredient, the carbon dots are doped in the carbon nitride material to form a carrier, and the metal ions are loaded on the carrier.

[0069] The metal ions are loaded on the carbon dot-doped carbon nitride material to improve the efficiency of photocatalytic water splitting to produce hydrogen. It can be seen that the above-mentioned carbon dot-carbon nitride material loaded with metal ions has both the function of producing hydrogen and loaded with metal ions, thus achieving in vivo / in vitro metal ion delivery and efficient hydrogen therapy. In addition, the experiment found that the carbon-based material has high biocompatibility, biosafety and bioavailability. At the same time, photocatalytic hydrogen production and metal ion death induction have a synergistic and mutually reinforcing effect, thereby having a good therapeutic effect on metal death-related diseases and / or hydrogen therapy.

[0070] In some embodiments of the present application, the above-mentioned carbon dot-carbon nitride material loaded with metal ions includes any one or more of carbon dot-carbon nitride material loaded with copper ions, carbon dot-carbon nitride material loaded with iron ions, carbon dot-carbon nitride material loaded with manganese ions, carbon dot-carbon nitride material loaded with zinc ions, and carbon dot-carbon nitride material loaded with platinum ions. Materials loaded with different metal ions exert the corresponding metal ion death mechanism to achieve the effect of treating the corresponding disease.

[0071] The metal ion-loaded carbon dot-carbon nitride material used in the present application can be a conventional metal ion-loaded carbon dot-carbon nitride material or a metal ion-loaded carbon dot-carbon nitride material prepared by a conventional method. In some embodiments of the present application, the above-mentioned metal ion-loaded carbon dot-carbon nitride material is a metal ion-loaded carbon dot-carbon nitride nanosheet, and the nanosheet structure is more conducive to metal ion delivery and hydrogen generation.

[0072] The metal ions are mainly used to play a metal death role. In some embodiments of the present application, in the above-mentioned carbon dot-carbon nitride material loaded with metal ions, the mass content of the metal ions is 1.0wt%-3.0wt%.

[0073] In some embodiments of the present application, in order to facilitate the delivery of the material in vivo and improve the delivery efficiency of the material, the particle size of the carbon dot-carbon nitride material loaded with metal ions is selected to be between 60 nm and 200 nm.

[0074] In some embodiments of the present application, the dosage form of the pharmaceutical composition is any one of an oral preparation, an injection preparation, an inhalation preparation, and an external preparation. Those skilled in the art select different excipients or adjuvants to form the above-mentioned different dosage forms. Preferably, the dosage form of the above-mentioned drug combination is an injection preparation.

[0075] Dosage forms suitable for oral administration may be presented as discrete units, such as capsules, cachets or tablets, each containing a predetermined amount of the active ingredient; as a powder or granules; as a solution or suspension in an aqueous or non-aqueous liquid; or as an oil-in-water liquid emulsion or a water-in-oil liquid emulsion. Or they may be prepared into oral formulations by other known techniques.

[0076] In some embodiments, the pharmaceutical composition may be in the form of a sterile injectable preparation, such as a sterile injectable aqueous or oleaginous suspension.

[0077] In some embodiments, the pharmaceutical composition can be an inhalant, which can be a preparation suitable for intrapulmonary or intranasal administration, and such preparations generally have a particle size in the range of 0.1-500 microns, such as 0.5, 1, 30, 35 microns, etc., which is rapidly inhaled through the nasal passage or administered by oral inhalation to reach the alveoli. The material as an active ingredient in some embodiments of the present application has a scale that can be used for intrapulmonary or intranasal administration, and can be used for intrapulmonary or intranasal administration.

[0078] In some embodiments, the pharmaceutical composition may be formulated for rectal administration which may be presented as a suppository with a suitable base containing, for example, cocoa butter or a salicylate.

[0079] In some embodiments, the pharmaceutical composition may be a formulation suitable for parenteral administration including aqueous and non-aqueous sterile injections.

[0080] In some embodiments of the present application, the diseases for which the pharmaceutical composition is used to treat or prevent include diseases associated with abnormal metal ion levels and / or diseases that can be treated with hydrogen.

[0081] In some embodiments of the present application, the above-mentioned diseases related to metal death include any one or more of diseases related to abnormal copper ion levels, diseases related to abnormal iron ion levels, diseases related to abnormal manganese ion levels, diseases related to abnormal zinc ion levels and diseases related to abnormal platinum ion levels; optionally, the diseases related to abnormal metal ions include any one or more of cardiovascular diseases, neurodegenerative diseases, tumors and cancers, and are further preferably any one or more of breast cancer, colorectal cancer, lung cancer, liver cancer, prostate cancer, acute myeloid leukemia, glioma, neurodegenerative diseases, and bacterial infections; diseases treated with hydrogen include any one or more of cardiovascular diseases, respiratory diseases, blood diseases, metabolic diseases, infections and neurodegenerative diseases; cardiovascular diseases include atherosclerosis, hypertension, hypercholesterolemia and diabetic vascular disease; respiratory diseases include any one or more of upper respiratory tract infection, chronic obstructive pulmonary disease, pneumonia, bronchial asthma and lung cancer; blood diseases include any one or more of aplastic anemia, internal bleeding, pulmonary embolism, venous sinus thrombosis and cerebral infarction; neurodegenerative diseases include any one or more of Alzheimer's disease, Parkinson's disease and Huntington's disease (HD). All of the above diseases can be treated or assisted in treatment with hydrogen. The material used in this application is used as a photocatalyst, which decomposes water to produce hydrogen under the action of photocatalysis, and the produced hydrogen is used to achieve the therapeutic effect on the above diseases.

[0082] The third embodiment of the present application also provides a method for treating a disease, comprising administering a therapeutically effective amount of a material to a patient in need thereof, wherein the material is the material provided by any of the above embodiments. The disease is any disease described in any of the above embodiments.

[0083] The carbon-based material used in the present application can be a conventional carbon dot-carbon nitride material loaded with metal ions or a carbon dot-carbon nitride material loaded with metal ions prepared by conventional methods. A preparation method of a carbon dot-carbon nitride material loaded with metal ions is provided below to facilitate technical personnel in this field to implement the technical solution of the present application.

[0084] The preparation method comprises:

[0085] adding urea to the carbon dot solution to form a reaction solution;

[0086] The reaction solution is heated to 500° C.-600° C. and maintained at the temperature for 2-4 hours to obtain a crude product;

[0087] The crude product is refluxed in a nitric acid solution for a first predetermined time, and after the reflux is completed, it is washed to neutrality to obtain a first slurry, and the first slurry is subjected to a first solid-liquid separation to obtain a solid separated product. In some embodiments, the first solid-liquid separation is centrifugal separation, and the centrifugal speed is 10000rpm-12000rpm;

[0088] dispersing the solid isolate in water to form a second slurry;

[0089] The second slurry is subjected to ultrasonic treatment for a second predetermined time to obtain a suspension. In some embodiments, the second predetermined time is 8-15 hours;

[0090] The suspension is subjected to a second solid-liquid separation to obtain a liquid component, wherein the liquid component contains carbon dot-doped carbon nitride. In some embodiments, the second solid-liquid separation is centrifugal separation, preferably at a speed of 4000 rpm-6000 rpm for 10 minutes to separate large particles.

[0091] The liquid component is mixed with the metal salt and subjected to ultrasonic treatment for a third predetermined time to obtain a dispersion, preferably, the third predetermined time is 1 hour to 3 hours; in this process, the metal salt can be appropriately added in excess to increase the loading amount of the metal ion, and the mass content of the metal ion in the finally obtained carbon-based material is adjusted to 1.0wt%-3.0wt% by controlling the quality of the added metal salt and the third predetermined time of ultrasonic treatment;

[0092] Centrifuging the dispersion to obtain a solid collection, preferably, the rotation speed of the centrifugal separation is 10000 rpm-14000 rpm, and the time is 15 min-30 min;

[0093] The collected solids are washed and dried to obtain the material of the present application.

[0094] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples, but the scope of the present invention is not limited to these embodiments.

[0095] Some experimental supplies: citric acid, hydrogen peroxide, methylene blue, urea, cupric chloride, and chloroplatinic acid were from Aladdin Reagent (Shanghai) Co., Ltd. Indocyanine green was from ACROS ORGANICS. 2',7'-Dichlorodihydrofluorescein diacetate (DCFH-DA) and ATP detection kit were from Shanghai Biotech Biotechnology Co., Ltd. JC-1 was from MedChemExpress; BODIPYTM 581 / 591C11 (lipid peroxidation probe) was from thermo fisher scientific. Ultrapure water was from ELGA LabWater purification system.

[0096] Example 1

[0097] Synthesis of carbon dots

[0098] Weigh citric acid (2 g) and urea (0.5 g) and dissolve them in 25 mL of ultrapure water to form a mixed solution. The mixed solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180°C for 12 hours. The resulting solution was collected, dialyzed for three days using a dialysis bag (MWCO 500-1000Da, Spectrum), and vacuum freeze-dried to obtain carbon dot black powder.

[0099] Synthesis of Carbon Nitride (CN)

[0100] Carbon nitride: 5 g of urea was placed in an alumina crucible with a lid, heated to 550 °C in a muffle furnace at a rate of 5 °C / min and maintained for 3 h to obtain carbon nitride (C3N4).

[0101] Carbon dot doped carbon nitride (CDCN): 5 g of urea was added to 2.5 mL of 0.6 mg / mL carbon dot solution to form a mixture. The mixture was transferred to a crucible, heated to 550 ° C at a rate of 5 ° C / min in a muffle furnace, and maintained at this temperature for 3 hours to obtain a crude product. The crude product was refluxed in a 5 mol / L nitric acid solution for 24 hours, and the refluxed material was washed with water to pH = 7 after reflux, and then centrifuged at 11000 rpm to obtain a precipitate, and the obtained precipitate was redispersed in water, and a suspension was obtained after continuous ultrasonic treatment for 10 hours. The suspension was centrifuged at 5000 rpm for 10 minutes to remove large particles, and the supernatant was collected, which contained carbon dot doped carbon nitride nanosheets.

[0102] Copper loaded on carbon dot doped carbon nitride (Cu@CDCN): 1 mg / mL of the synthesized carbon dot doped carbon nitride nanosheets was mixed with a CuCl2 aqueous solution (0.1 M). After ultrasonic treatment for 2 hours, the solution was centrifuged and washed several times with ultrapure water to remove the unloaded CuCl2. The resulting solution was copper loaded carbon dot doped carbon nitride nanosheets (Cu@CDCN). Finally, the product was dried in a vacuum oven overnight to obtain a powder sample, and the loading amount of Cu@CDCN was determined to be 1.8 wt% by ICP-OES measurement.

[0103] Material Testing:

[0104] 1) Projection electron microscope test

[0105] Carbon nitride, carbon dot-doped carbon nitride, and copper-loaded carbon dot-doped carbon nitride nanosheets were tested using transmission electron microscopy and the test results are recorded in Figure 1 Among them, a) is the transmission electron microscopy image of carbon nitride (CN), b) is the transmission electron microscopy image of carbon dot-doped carbon nitride (CDCN), and c) is the transmission electron microscopy image of copper-loaded carbon dot-doped carbon nitride nanosheets (Cu@CDCN). It can be seen that all three materials have a thin layer morphology of about 100 nm, that is, the doping of Cu and carbon dots does not affect the lamellar structure of CN.

[0106] 2) Hydration particle size distribution test

[0107] The hydrated particle size distribution of CN, CDCN and Cu@CDCN aqueous solutions was measured by Malvern laser particle size analyzer, and the results were recorded in Figure 2 In, according to Figure 2 It can be seen that the hydrated particle sizes of the three materials are distributed between 60nm and 200nm, which is consistent with Figure 1 The TEM results correspond to those of

[0108] 3) Water dispersibility test

[0109] Digital cameras were used to obtain digital photos of aqueous solutions of CN, CDCN, and Cu@CDCN at a concentration of 1 mg / mL and recorded in Figure 3 , Figure 3 It shows that the synthesized samples have good water dispersibility.

[0110] 4) XRD ray diffraction test

[0111] X-ray diffraction tests were performed on CN, CDCN and Cu@CDCN, and the obtained X-ray diffraction patterns were recorded in Figure 4 middle, Figure 4 The XRD diffraction spectrum of each material shows that the characteristic peak is located at 27.5°, which originates from the interplanar stacking of the graphite structure in CN, representing the synthesis of a typical CN structural unit. The decrease in the diffraction intensity of CDCN and Cu@CDCN indicates that the doping of carbon dots and Cu affects the crystallinity of CN.

[0112] 5) UV-visible light absorption test

[0113] The UV-visible absorption of CN, CDCN and Cu@CDCN was tested by UV-visible spectrophotometer, and the obtained UV-visible absorption spectra were recorded in Figure 5 . Figure 5 It is shown that the doping of carbon dots and Cu increases the absorption capacity of CN and broadens the absorption spectrum.

[0114] 6) Photocatalytic hydrogen production test

[0115] Test conditions: Kessil A160WE photocatalytic lamp provides LED light source, wavelength 400-500nm, intensity 30mW / cm 2 , irradiate methylene blue solution for 0-30min, the concentration of CN, CDCN, and Cu@CDCN in the methylene blue solution is 0.2mg / mL respectively, and detect the change of the absorption peak of methylene blue at 663nm to reflect the photocatalytic activity of CN, CDCN, and Cu@CDCN. The photocatalytic hydrogen production ability of CN, CDCN, and Cu@CDCN is recorded in Figure 6 In, through Figure 6 It can be seen that CDs doping increases the photocatalytic ability of CN. In addition, Cu anchoring further increases the photocatalytic water splitting ability.

[0116] 7) Photocatalytic ability to produce hydrogen peroxide

[0117] CN, CDCN and Cu@CDCN aqueous solution (0.5 mg / mL) were used as photocatalysts under the light of LED (400-500 nm, Kessil A160WE, 30 mW / cm 2 ) was used to detect the ability to generate hydrogen peroxide. After different irradiation times (0-30 minutes), the concentration of hydrogen peroxide was measured using a hydrogen peroxide detection kit (S0038, Beyotime Biotech).

[0118] Figure 7 The photocatalytic hydrogen peroxide production capabilities of CN, CDC and Cu@CDCNN in Example 1 are shown. Figure 7 It can be seen that CDs doping increases the ability of CN to produce hydrogen peroxide through photocatalysis. In addition, the anchoring of Cu helps to decompose the byproduct of photocatalysis - hydrogen peroxide.

[0119] 8) Determination of the ability to consume reduced glutathione (GSH)

[0120] A 200 μg / mL aqueous solution of the nanomaterial to be tested was mixed with GSH (100 μM) under vibration for 10 min. Then, the solution was centrifuged (14000 rpm, 10 min), and the supernatant was subjected to glutathione determination using a reduced glutathione assay kit (Ellmann probe (5,5′-dithiobis-(2-nitrobenzoic acid)). The content of reduced glutathione (GSH) consumed by CN, CDCN and Cu@CDCN obtained by the test was recorded in Figure 8 In the table, *** indicates P < 0.001, indicating a significant difference (the P value was obtained by the two-tailed Student's ttest method).

[0121] Due to Cu 2+ It can react with reduced glutathione and consume reduced glutathione. Reduced glutathione is the key to maintaining the redox balance in cells. The consumption of reduced glutathione can cause oxidative stress in cells and promote copper-induced cancer cell death.

[0122] Cell experiments:

[0123] For flow cytometry experiments, 4T1 cells were plated at 10 5 Cells were seeded in 24-well plates at 37°C for 12 hours, and then cultured with medium containing CDCN (50 μg / mL) for 0, 1, 2, 4, 6, 8, and 10 hours, washed three times with PBS, and the cells were collected for flow cytometry testing.

[0124] For confocal fluorescence colocalization imaging, 4T1 cells were seeded in 30 mm glass-bottom culture dishes at an initial density of 10 cells per dish. 5 4T1 cells were cultured at 37°C for 12 hours to adhere to the wall. The culture medium containing CDCN (50 μg / mL) was used for another 8 hours. Lysosomes and mitochondria were then stained with Lysosome Tracker Red (Beyotime) and Mitochondria Green (Invitrogen), respectively. After removing the dye, the cells were rinsed three times with PBS and observed on a confocal laser scanning microscope (Zeiss LSM 880+Airyscan).

[0125] Fig. 9 The cellular uptake of CDCN is shown, where Fig. 9 a) Cell internalization of CDCN nanosheets after incubation with 4T1 cells for different time periods was verified by flow cytometry and confocal microscopy. Fig. 9 b) and c) Cell localization behavior of CDCN nanosheets after incubation with 4T1 cells for 8 h, and the fluorescence emission of the material itself was used to detect the uptake.

[0126] pass Fig. 9 As can be seen from b) and 9c, the nanosheets were quickly and completely taken up by the cells and localized in the lysosomes in 8 h, indicating that the nanosheets entered the cells via endocytosis of the lysosomes.

[0127] Test on the effect on 4T1 cell activity

[0128] Different concentrations of CN, CDCN, and Cu@CDCN (concentration range 12.5-200 μg / mL) were co-incubated with 4T1 cells for 8 h and then illuminated or not. The illumination condition was 30 mW / cm 2, illuminate for 10 min, continue culturing for 24 h, and then use CCK-8 (cell proliferation and cytotoxicity detection kit) to detect cell activity.

[0129] Fig.10 Figures a), b), and c) show the effects of different concentrations of CN, CDCN, and Cu@CDCN on the activity of 4T1 cells before and after illumination. It can be seen that a single photocatalytic CDCN can inhibit cell activity, and the combined action of Cu and CDCN (Cu@CDCN plus illumination group) exhibits the strongest inhibition efficiency and more significantly kills cancer cells.

[0130] Annexin V-FITC / PI kit was used to analyze the 4T1 cells after different treatments by flow cytometry. The analysis results are shown in Fig.11 .according to Fig.11 It can be seen that Cu@CDCN induced the most early and late apoptosis in 4T1 after light treatment, and the ratio was consistent with the CCK-8 results.

[0131] Determination of intracellular GSH

[0132] 4T1 cells were plated at 8 × 10 5 The density of 100 μg / cm2 was inoculated in a 6-well culture dish. After 8 hours of incubation with CN, CDCN and Cu@CDCN (0.1 mg mL-1), LED (30 mW / cm 2 ) for 10 minutes. Then, the cells were lysed and centrifuged at 14000 rpm for 10 minutes. Finally, the glutathione in the supernatant was detected using a reduced glutathione detection kit (Nanjing Jiancheng Bioengineering Institute). The decrease in absorbance at 405 nm was collected to calculate the consumption of GSH and recorded in Fig.12 middle. Fig.12 It is shown that Cu@CDCN consumes the most GSH, indicating that it has the strongest activity.

[0133] Test the content of intracellular ATP before and after light exposure

[0134] The intracellular ATP level was detected by ATP detection kit (S0027, Beyotime Biotech). 4T1 cells were cultured at 8×10 5 The density of 100 μg / mL was sown in a 6-well culture dish. After 8 hours of incubation with CN, CDCN and Cu@CDCN (0.1 mg / mL), LED (30 mW / cm 2 ) for 10 minutes. After 3 hours, 4T1 cells were lysed and the supernatant was collected by centrifugation immediately. ATP levels were measured using an ATP detection kit. The test results were recorded in Fig.13The results showed that the intracellular ATP content decreased significantly after photocatalytic treatment, proving the role of photocatalytic hydrogen production, which is consistent with the fact that hydrogen treatment can affect the intracellular ATP content.

[0135] Intracellular reactive oxygen species level test

[0136] 4T1 cells were cultured at 10 5 The 4T1 cells were cultured in a 30 mm glass bottom dish at a density of 100 cells / mL. Then, 4T1 cells were treated with CN, CDCN, and Cu@CDCN (100 μg mL-1) for 8 h and illuminated with LED (30 mW / cm 2 ) for 10 minutes or without illumination. Then, cells were immediately stained with DCFH-DA (5 μM)—a reactive oxygen species probe and Hoechst 33342 (10 μg / mL)—a commercial dye for the nucleus for 30 minutes, respectively, and DCFH fluorescence emitted by ROS was collected using a laser scanning confocal microscope (Zeiss LSM 880+Airyscan). Flow cytometry was used to quantify the production of ROS.

[0137] Test results are recorded in Fig.14 Among them, the intracellular reactive oxygen level in the cells treated with Cu@CDCN was the highest, which was due to the consumption of GSH by copper and the Fenton reaction, which could increase the intracellular reactive oxygen level. The photocatalytic effect further promoted the increase in the reactive oxygen level caused by copper.

[0138] Cellular lipid peroxidation level test

[0139] 4T1 cells were seeded in 24-well culture dishes, with 10 cells per well. 5 Then, the cells were treated with CN, CDCN, and Cu@CDCN (0.1 mg / mL) for 8 h and then illuminated with LED (30 mW / cm 2 ) for 10 minutes. After culturing for another 16 hours, the cells in the observation wells were rinsed three times with PBS, stained with BODIPY 581 / 591C11, and then analyzed by flow cytometry. BODIPY 581 / 591C11 was used as the test kit for the lipid peroxidation level of the cells.

[0140] Test results are recorded in Fig.15 middle, Fig.15 It shows that the lipid peroxidation level of cells treated with Cu@CDCN is the highest, which is due to the production of a large amount of reactive oxygen species. Cu@CDCN treatment induced a significant increase in the level of cellular lipid peroxidation.

[0141] 4T1 cell cycle analysis and quantification

[0142] The cell cycle phase was analyzed by propidium iodide staining. 4T1 cells were cultured in 12-well culture plates (5 × 10 5 cells / well), treated with CN, CDCN, and Cu@CDCN (0.05 mg / mL) for 8 h, and then illuminated with LED (30 mW / cm 2 ) for 10 minutes. After 16 hours of culture, the cells were collected and rinsed with PBS, and then fixed with pre-cooled ethanol at 4°C for 24 hours. After washing with PBS and BD staining buffer (554656, BD Pharmingen), the cells were stained with propidium iodide / RNase staining buffer (550825, BD Pharmingen) at room temperature for 30 minutes and immediately analyzed by flow cytometry.

[0143] Fig.16 a) shows the cell cycle analysis results of CN, CDCN and Cu@CDCN (50 μg / mL) and light-treated thick 4T1 cells, and b) shows the corresponding quantitative analysis results.

[0144] It can be seen that CDCN as a single photocatalytic hydrogen production treatment will block the cell cycle in the G2 phase, and copper treatment mainly causes cells to be retained in the G1 phase. The synergistic effect of the two (Cu@CDCN) leads to a decrease in the S phase (DNA synthesis phase) of cells, and obvious retention in the G1 and G2 phases.

[0145] Scratch healing assay

[0146] 4T1 cells were plated at 10 per well 6 The cells were inoculated in a 6-well culture dish at a density of 100 μL. The floating cells were washed off by scratching with a 200 μL pipette tip. After 8 hours of culture with pure culture medium and Cu@CDCN, the cells were illuminated with LED (30 mW / cm 2 ) for 10 minutes. The scratched area was photographed under a microscope at 0, 12, and 24 hours after scratching, and the scratch healing rate was quantitatively analyzed using ImageJ software.

[0147] Fig.17 The left figure shows the scratch healing experiment results of 4T1 cells after different concentrations of Cu@CDCN and light treatment, and the right figure shows the quantitative analysis results of the scratch healing rate obtained by ImageJ software analysis.

[0148] 4T1 cells have high migration and metastasis abilities. Inhibiting migration ability is a key indicator for evaluating the therapeutic effect of anticancer drugs. The effect of treatment on the migration ability of 4T1 cells was evaluated by scratch test. The results show that Cu@CDCN can inhibit the healing of 4T1 scratches and inhibit the lateral migration rate after light treatment.

[0149] Mitochondrial damage test

[0150] JC-1 was selected as a probe to assess mitochondrial damage. 4T1 cells were plated at 10 5 The number of cells was inoculated in a 24-well plate and treated with CN, CDCN and Cu@CDCN (50 μg / mL) for 8 h. 2 ) were irradiated for 10 minutes and then cultured for 16 hours, then stained with JC-1 dye for 30 minutes. Finally, the changes in mitochondrial membrane potential were detected by flow cytometry.

[0151] Fig.18 The results of the mitochondrial damage test are shown, wherein a) JC-1 staining is used to analyze the mitochondrial membrane potential after different treatments using a flow cytometer. The ratio of JC-1 aggregates to monomers (red / green fluorescence ratio) is an indicator of mitochondrial membrane polarization. b) The FDX1 protein content of 4T1 cells after different treatments is shown.

[0152] The targets of hydrogen therapy and copper death are both mitochondria. JC-1 evaluated the changes in mitochondrial membrane potential after synergistic treatment, which means that the synergistic effect of copper death and hydrogen therapy caused serious mitochondrial damage. In addition, FDX1, as an upstream regulator of copper death, has been proven to be a marker of copper death. Protein immunoblotting (Western Blot, WB) experiments have proved that Cu@CDCN can downregulate the expression of FDX1 and initiate the process of copper death. On the other hand, a single photocatalytic process also affects the expression of FDX1. In summary, the experiments have proved that copper death and photocatalytic hydrogen production have excellent synergistic effects.

[0153] Animal experiments

[0154] Safety evaluation

[0155] Female BALB / c mice were intravenously injected with Cu@CDCN (10 mg / mL). Blood samples were collected on days 0, 3, and 7 after injection. After centrifugation at 4°C for 20 min, plasma was collected for blood biochemical analysis. The concentrations of aspartate aminotransferase (AST), alkaline phosphatase (ALP), and alanine aminotransferase (ALT) were measured using an automatic biochemical analyzer (Mindray, BS-220) to evaluate liver function. Whole blood was also collected for leukocyte, erythrocyte, and platelet analysis to evaluate biosafety.

[0156] Fig.19 The results of blood routine analysis of mice are shown. Fig. 20 Results of serum analysis of mice are shown. Fig.21 The results of the hemolytic experiment in mice are shown.

[0157] Figures 19 to 21The results showed the biosafety of Cu@CDCN materials, that is, it did not cause liver and kidney damage at a dose of 10 mg / kg, and the indicators of blood routine and serum biochemical analysis were all within the normal range. There was no obvious hemolysis within the concentration range of 200 μg / mL, which is a safe and biocompatible carbon-based nanoformulation suitable for in vivo treatment evaluation.

[0158] Intratumoral analysis of tumor-bearing mice:

[0159] Female BALB / c mice were injected in the right axilla with 5 × 10 6 4T1 cells were used to construct 4T1 tumor-bearing mice. When the tumor volume reached 80 mm 3 Cu@CDCN-ICG solution (5 mg / kg) was intravenously injected at 1, 2, 3, 6, 9, 12, 18, and 24 hours after injection. 24 hours after injection, mice were euthanized, and major organs and tumors were collected. In vivo and in vitro fluorescence images were obtained using the IVIS in vivo imaging system.

[0160] After Cu@CDCN was labeled with indocyanine green (ICG), fluorescence imaging was performed in 4T1 tumor-bearing mice via tail vein administration. The results were recorded in Fig. 22 In figure a).

[0161] The mean fluorescence intensity in the tumor at different times after intravenous injection of Cu@CDCN-ICG was analyzed and the results were recorded in Fig. 22 In the figure b).

[0162] Ex vivo fluorescence images of major organs and tumors of tumor-bearing mice were analyzed and the results were recorded in Fig. 22 c) in the figure.

[0163] At 24h and 36h after Cu@CDCN-ICG injection, the corresponding mean fluorescence intensity was analyzed and the results were recorded in Fig. 22 d) in the figure.

[0164] Fig. 22 The results showed that Cu@CDCN reached maximum intratumoral enrichment 3 hours after tail vein injection and had a long-term intratumoral retention effect within 36 hours.

[0165] Analysis of in vivo solid tumor treatment effects

[0166] In vivo treatment

[0167] For the treatment of 4T1 tumors, 5 × 10 64T1 cells were injected into the axilla of female BALB / c mice to prepare mice bearing 4T1 tumors. When the tumor size reached about 100 cubic millimeters, treatment was performed. The mice were randomly divided into 6 groups (n = 5 samples per group) and injected with 100 μL PBS or CDCN and Cu@CDCN nanosheets (10 mg / kg) through the tail vein on days 1, 3, 5, and 8, respectively. The tumor site was then irradiated with or without 400-500 nm LED (30 mW / cm 2 , 15 minutes). The body weight and tumor size of each mouse were recorded every two days. After 2 weeks of treatment, all mice were humanely killed.

[0168] Fig.23 a) shows the treatment method for tumor-bearing mice. b) shows the change of 4T1 tumor volume during treatment. c) shows the weight curve of each group of mice after 15 days of treatment. d) shows the mass of 4T1 tumor after 15 days of treatment. e) shows the photos of 4T1 tumors extracted after 15 days of treatment (n=5 biological independent samples). I Control is the PBS injection group, IIcontrol+L is the light treatment group after PBS injection, IIICDCN is the CDCN injection group, IV CDCN+L is the light treatment group after CDCN injection, V CuCDCN is the Cu@CDCN injection group, and VI CuCDCN+L is the light treatment group after Cu@CDCN injection.

[0169] The treatment group with tail vein injection of Cu@CDCN and additional light irradiation (VI CuCDCN+L is the light treatment group after injection of Cu@CDCN) showed the most significant tumor inhibition effect, reflecting that the synthesized Cu-loaded carbon-based nano-photocatalytic system has excellent in vivo / in vitro anti-tumor effects. It also proves the synergistic effect of photocatalysis and copper death, which has a mutually reinforcing effect.

[0170] Comparative Example 1

[0171] Synthesis of carbon nitride (CDCN) with different carbon dot doping amounts: 5g of urea was added to 2.5mL of 0.2-0.6mg / mL carbon dot solution (0.2 was named CDCN-1, 0.6 was named CDCN-2) to form a mixture. The mixture was transferred to a crucible, heated to 550°C at a rate of 5°C / min in a muffle furnace, and maintained at this temperature for 3 hours to obtain a crude product. The crude product was refluxed in a 5mol / L nitric acid solution for 24 hours, and the refluxed material was washed with water to pH=7 after reflux, and then centrifuged at 11000rpm to obtain a precipitate, which was redispersed in water and subjected to continuous ultrasonic treatment for 10 hours to obtain a suspension. The suspension was centrifuged at 5000rpm for 10 minutes to remove large particles, and the supernatant was collected, which contained carbon dot-doped carbon nitride nanosheets.

[0172] Material Testing:

[0173] 1) Photocatalytic hydrogen production test

[0174] Test conditions: Kessil A160WE photocatalytic lamp provides LED light source, wavelength 400-500nm, intensity 30mW / cm 2 , irradiate methylene blue solution for 0-30min, the concentration of CN, CDCN, and Cu@CDCN in the methylene blue solution is 0.2mg / mL respectively, and detect the change of the absorption peak of methylene blue at 663nm to reflect the photocatalytic activity of CN, CDCN, and Cu@CDCN. The photocatalytic hydrogen production ability of CN, CDCN-1, and CDCN-2 is recorded in Fig.24 In, through Fig.24 It can be seen that CDs doping increases the photocatalytic ability of CN. In addition, the doping amount of different carbon dots has no obvious effect on the photocatalytic water splitting ability.

[0175] 2) Photocatalytic ability to produce hydrogen peroxide:

[0176] CN, CDCN-1, and CDCN-2 aqueous solutions (0.5 mg / mL) were used as photocatalysts under the illumination of LED (400-500 nm, Kessil A160WE, 30 mW / cm 2 ) was used to detect the ability to generate hydrogen peroxide. After different irradiation times (0-30 minutes), the concentration of hydrogen peroxide was measured using a hydrogen peroxide detection kit (S0038, Beyotime Biotech). Fig.25 The photocatalytic hydrogen peroxide production capabilities of CN, CDCN-1, and CDCN-2 in Comparative Example 1 are shown. Fig.25 It can be seen that CDs doping increases the ability of CN to photocatalytically produce hydrogen peroxide, but the doping amounts of different carbon dots have no obvious effect on the production of hydrogen peroxide.

[0177] Example 2

[0178] Effects of different metal doping on glutathione consumption and cytotoxicity of carbon dots doped with C3N4.

[0179] Copper (Cu@CDCN) or iron (Fe@CDCN) loaded on carbon dot-doped carbon nitride: 1 mg / mL of the synthesized carbon dot-doped carbon nitride nanosheets was mixed with CuCl2 or FeCl3 aqueous solution (0.1M). After ultrasonic treatment for 2 hours, the solution was centrifuged and washed several times with ultrapure water to remove the unloaded metal ions. The resulting solution was copper (Cu@CDCN) or iron (Fe@CDCN) loaded carbon dot-doped carbon nitride nanosheets. Finally, the product was dried in a vacuum oven overnight to obtain a powder sample.

[0180] 1) Test of the ability to consume reduced glutathione (GSH)

[0181] The aqueous solution of 200 μg / mL of the nanomaterial to be tested was mixed with GSH (100 μM) under vibration for 10 min. Then, the solution was centrifuged (14000 rpm, 10 min), and the supernatant was subjected to glutathione determination using a reduced glutathione determination kit (Ellmann probe (5,5′-dithiobis-(2-nitrobenzoic acid)). The content of reduced glutathione (GSH) consumed by CN, CDCN, Fe@CDCN and Cu@CDCN obtained by the test was recorded in Fig.26 In. From Fig.26 It can be seen that Cu 2+ and Fe 3+ The load of Cu significantly increased the ability to consume GSH, and 2+ Shows better performance than Fe 3+ Stronger ability to consume GSH.

[0182] 2) Test on the effect on 4T1 cell activity

[0183] CN, CDCN, Fe@CDCN and Cu@CDCN were co-incubated with 4T1 cells for 8 h and then treated with or without illumination. The illumination condition was 30 mW / cm 2 , illuminated for 10 min, and then cultured for 24 h before using CCK-8 (cell proliferation and cytotoxicity detection kit) to detect cell activity. The results were recorded in Fig.28 middle. Fig.28 The figure shows the effects of different concentrations of CN, CDCN, Fe@CDCN and Cu@CDCN on the activity of 4T1 cells before and after illumination. It can be seen that the Cu loading shows a stronger inhibitory efficiency than Fe and kills cancer cells more significantly.

[0184] 3) Determination of intracellular GSH

[0185] 4T1 cells were plated at 8 × 10 5 The cells were inoculated at a density of 100 μg / mL in a 6-well culture dish. After culturing with CN, CDCN, Fe@CDCN, and Cu@CDCN (0.1 mg / mL) for 8 h, they were irradiated with LED (30 mW / cm2) for 10 min. Then, the cells were lysed and centrifuged at 14,000 rpm for 10 min. Finally, the glutathione in the supernatant was detected using a reduced glutathione detection kit (Nanjing Jiancheng Bioengineering Institute). The decrease in absorbance at 405 nm was measured to calculate the consumption of GSH. The results were recorded in Fig.28 middle.

[0186] Fig.28 It is shown that Cu loading exhibits stronger glutathione consumption ability than Fe, *** indicates P<0.001, indicating a significant difference; ns indicates no significant difference (P value was obtained by two-tailed Student's t test method).

[0187] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. Use of a carbon-based material in the preparation of a drug for treating or preventing diseases, wherein the diseases include diseases associated with abnormal metal ion levels and / or diseases treated with hydrogen, wherein the carbon-based material is a carbon dot-carbon nitride material loaded with metal ions, wherein the carbon dots are doped in the carbon nitride material to form a carrier, and the metal ions are loaded on the carrier.

2. The use according to claim 1, characterized in that: The diseases associated with abnormal ion levels include any one or more of diseases associated with abnormal copper ion levels, diseases associated with abnormal iron ion levels, diseases associated with abnormal manganese ion levels, diseases associated with abnormal zinc ion levels, and diseases associated with abnormal platinum ion levels; optionally, the diseases associated with abnormal metal ions include any one or more of cardiovascular diseases, neurodegenerative diseases, tumors, and cancers, and are further preferably any one or more of breast cancer, colorectal cancer, lung cancer, liver cancer, prostate cancer, acute myeloid leukemia, glioma, neurodegenerative diseases, and bacterial infections; the diseases treated with hydrogen include cardiovascular diseases, The invention relates to a method for treating a pulmonary embolism, wherein the present invention comprises any one or more of cardiovascular diseases, atherosclerosis, hypertension, hypercholesterolemia and diabetic vascular disease; the respiratory diseases comprise any one or more of upper respiratory tract infection, chronic obstructive pulmonary disease, pneumonia, bronchial asthma and lung cancer; the blood diseases comprise any one or more of aplastic anemia, internal hemorrhage, pulmonary embolism, venous sinus thrombosis and cerebral infarction; the neurodegenerative diseases comprise any one or more of Alzheimer's disease, Parkinson's disease and Huntington's disease (HD).

3. The use according to claim 1 or 2, characterized in that: The metal ion-loaded carbon dot-carbon nitride material includes any one or more of a copper ion-loaded carbon dot-carbon nitride material, an iron ion-loaded carbon dot-carbon nitride material, a manganese ion-loaded carbon dot-carbon nitride material, a zinc ion-loaded carbon dot-carbon nitride material, and a platinum ion-loaded carbon dot-carbon nitride material.

4. The use according to any one of claims 1 to 3, characterized in that The metal ion-loaded carbon dot-carbon nitride material is a metal ion-loaded carbon dot-carbon nitride nanosheet.

5. The use according to any one of claims 1 to 4, characterized in that In the metal ion-loaded carbon dot-carbon nitride material, the mass content of the metal ions is 1.0 wt%-3.0 wt%.

6. The use according to any one of claims 1 to 5, characterized in that The particle size of the carbon dot-carbon nitride material loaded with metal ions is between 60nm and 200nm.

7. A pharmaceutical composition, characterized in that The pharmaceutical composition comprises a carbon dot-carbon nitride material loaded with metal ions and a pharmaceutically acceptable excipient or auxiliary material, wherein the carbon dot-carbon nitride material loaded with metal ions serves as an active ingredient, carbon dots are doped in the carbon nitride material to form a carrier, and the metal ions are loaded on the carrier.

8. The pharmaceutical composition according to claim 7, characterized in that The metal ion-loaded carbon dot-carbon nitride material includes any one or more of a copper ion-loaded carbon dot-carbon nitride material, an iron ion-loaded carbon dot-carbon nitride material, a manganese ion-loaded carbon dot-carbon nitride material, a zinc ion-loaded carbon dot-carbon nitride material, and a platinum ion-loaded carbon dot-carbon nitride material.

9. The pharmaceutical composition according to claim 7 or 8, characterized in that The metal ion-loaded carbon dot-carbon nitride material is a metal ion-loaded carbon dot-carbon nitride nanosheet.

10. The pharmaceutical composition according to any one of claims 7 to 9, characterized in that In the metal ion-loaded carbon dot-carbon nitride material, the mass content of the metal ions is 1.0wt%-3.0wt%; and / or the particle size of the metal ion-loaded carbon dot-carbon nitride material is between 60nm-200nm.

11. The pharmaceutical composition according to any one of claims 7 to 10, characterized in that The dosage form of the pharmaceutical composition is any one of an oral preparation, an injection preparation, an inhalation preparation, and an external preparation.

12. The pharmaceutical composition according to any one of claims 7 to 11, characterized in that The diseases that the pharmaceutical composition is used to treat or prevent include diseases associated with abnormal metal ion levels and / or diseases that can be treated with hydrogen.

13. The pharmaceutical composition according to claim 12, characterized in that The diseases associated with abnormal metal ion levels include any one or more of diseases associated with abnormal copper ion levels, diseases associated with abnormal iron ion levels, diseases associated with abnormal manganese ion levels, diseases associated with abnormal zinc ion levels, and diseases associated with abnormal platinum ion levels; optionally, the diseases associated with abnormal metal ion levels include any one or more of cardiovascular diseases, neurodegenerative diseases, tumors, and cancers, and are further preferably any one or more of breast cancer, colorectal cancer, lung cancer, liver cancer, prostate cancer, acute myeloid leukemia, glioma, neurodegenerative diseases, and bacterial infections; the diseases treated with hydrogen include cardiovascular diseases, any one or more of cardiovascular diseases, respiratory diseases, blood diseases, metabolic diseases, infections and neurodegenerative diseases; the cardiovascular diseases include any one or more of atherosclerosis, hypertension, hypercholesterolemia and diabetic vascular disease; the respiratory diseases include any one or more of upper respiratory tract infection, chronic obstructive pulmonary disease, pneumonia, bronchial asthma and lung cancer; the blood diseases include any one or more of aplastic anemia, internal hemorrhage, pulmonary embolism, venous sinus thrombosis and cerebral infarction; the neurodegenerative diseases include any one or more of Alzheimer's disease, Parkinson's disease and Huntington's disease (HD).